2019
DOI: 10.17116/jnevro2019119061152
|View full text |Cite
|
Sign up to set email alerts
|

Current approaches to the treatment and correction of Internet addiction

Abstract: 1 Институт эволюционной физиологии и биохимии им. И.М. Сеченова РАН, Санкт-Петербург, Россия; 2 Санкт-Петербургский государственный университет, Санкт-Петербург, Россия; 3 Северо-Западный государственный медицинский университет им. И.И. Мечникова, Санкт-Петербург, Россия; 4 Санкт-Петербургский государственный педиатрический медицинский университет, Санкт-Петербург, Россия РезюмеСогласно решению ВОЗ игровое расстройство, в том числе в форме интернет-аддикции (ИА) предполагается ввести в раздел «Импульсивные рас… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Studies were included if they fulfilled the following criteria: (1) used a validated scale to assess IAD; (2) reported the relationship between IAD and health risk behaviors; (3) were observational studies published up to Aug 2021; (4) had a Pearson or Spearman correlation coefficient (r) or odds ratios (ORs) available; (5) were published in Chinese or English.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were included if they fulfilled the following criteria: (1) used a validated scale to assess IAD; (2) reported the relationship between IAD and health risk behaviors; (3) were observational studies published up to Aug 2021; (4) had a Pearson or Spearman correlation coefficient (r) or odds ratios (ORs) available; (5) were published in Chinese or English.…”
Section: Methodsmentioning
confidence: 99%
“…Internet addiction disorder (IAD) is considered as an inability of individuals to control their internet use, resulting in marked distress and functional impairment in daily life such as psychological, social, academic, and professional problems (1). The overall prevalence of IAD ranges from 1.5 to 8.2% in the United States and Europe (2). IAD has attached much attention throughout the world among adolescents, with a prevalence of 7.9-16.0% (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the United States and Europe suggest that prevalence of internet addiction ranges from 1.5 to 8.2%. In Southeast Asia, the prevalence among young people can be as high as 20-30% (Egorov and Grechanyi, 2019). Internet overuse continues to increase due to the low cost, portability, and increasing sophistication of internet-related devices.…”
Section: Introductionmentioning
confidence: 99%
“…It has attracted much attention around the world ( 2 ). Previous researches suggested that the prevalence of IAD ranges from 1.5 to 8.2% in the United States and Europe, while in Southeast Asia, it could be as high as 20–30% among young people ( 3 ). The current study showed that the prevalence of IAD was 7.7% in Chinese college students ( 4 ).…”
Section: Introductionmentioning
confidence: 99%